The Progressive Islamic Movement : Study of Thinking Methodology by Abdullah Saeed - Imdad Rabbani (Dialogia, 2021)
The rapid of globalization and technological sophistication in the modernity era had made Islam and reality more tenuous, as if confused and weakened in responding to challenges and facing problems. This phenomenon encourages the spirit of contemporary Muslim philosophers in reconstructing Islamic foundations that are more responsive in dealing with problems. Abdullah Saeed introduced the trend of progressive Islam by using the progressive ijtihadi thinking method which tried to interpret the literalist-textualist teachings of classical Islam into a more humanist understanding of religion and is combined with contemporary scientific insights such as social sciences, humanities, and critical philosophy which makes Islamic religious teachings sallih likulli zaman wal makan. In the social landscape of humanity, progressive Islam considers the issue of riddah (apostasy) based on its socio-historical perspective, including affairs between humans and their Gods, not criminal acts so that the state does not have the authority to give death sentences for the perpetrators. Thus, the principles of Islamic teachings are able to go hand in hand with and not contradict UDHR article 18 by the United Nations. Therefore, this trend is expected to be able to answer important issues to find a solution, such as the issue of gender inequality, acts of violence against minorities, inheritance cases, or even an authoritarian state.